A Study on Stability and Passenger Capacity of Traditional River and Lake Boats - Hasanudin; Dwi Saputra Aditya; Nugroho Yulianto Ardi (BIO Web of Conferences)
Traditional boats are vital for many Indonesians, particularly river and lake passenger boats, which are essential transportation links in specific regions. However, the absence of regulated passenger capacity limits has compromised safety standards. This study aims to determine safe passenger capacities for river and lake boats through shipping risk and stability analyses. Using the minimum passenger area requirements from the Indonesian National Standard (SNI) and stability criteria from the Indonesian Classification Bureau (BKI), passenger capacities were calculated for various boat types across four waters: Lake Matano, the Mahakam River, the Indragiri River, and the Musi River. Boat lengths varied from 3 to 15 meters, and widths varied from 1 to 4.5 meters. The analysis of 15x4.5 meter boats shows that the speed boat is the most stable (134.7 kN.m) and accommodates the most passengers (56 people), the trimaran offers the most significant space despite having the lowest stability (62.0 kN.m), the long boat has the largest passenger area, and the catamaran has the lowest capacity (36 people). This research provides a framework for determining minimum passenger capacities based on boat dimensions and types, contributing to improved river and lake transportation safety standards in Indonesia.